An optimized 3D carbon matrix for high rate silicon anodes. Issue 53 (3rd July 2017) - Bai, Xuejun; Hou, Min; Yu, Zhaoyu; Liu, Chan; Cao, Hui; Wang, Dong; Fu, Junjie
Abstract : A 3D porous carbon matrix with silicon particles embedded shows high rate performance in a lithium ion battery. Abstract : A free-standing 3D porous carbon matrix was fabricated by a solution-based self-assembly process, using graphene aerogel (GA) as the matrix and CNTs as the structural enhancer. CNTs, with high electrical conductivity and mechanical strength, formed into a 3D scaffold along with GA. Silicon particles, with an oxidation coating (Si@SiO x ), were embedded into this GA matrix, and twined around the CNTs to increase conductivity of the Si@SiO x agglomerations and bonding force with the GA matrix. Electrodes constructed with the Si@SiO x /CNTs/GA containing 44 wt% Si@SiO x exhibit a stable storage capacity of 905 mA h g −1 at 4 A g −1 and 1500 mA h g −1 at 0.1 A g −1 after 150 th cycles with 93% capacity retention compared with the 10 th cycle capacity. These outstanding rate performances and cycling stability are attributed to the enhanced 3D porous matrix, which provides abundant internal space for volume changes of Si@SiO x, easy penetration of electrolyte, fast electron and ion transfer speed, and high mechanical strength.